ENHANCING ARGUMENTATIVE LITERACY THROUGH DEEP LEARNING-BASED INDONESIAN LANGUAGE INSTRUCTION AT SDN 3 KEMAWI - Sulistiawati, Erni; Abdul Wachid Bambang Suharto (Journal of Language and Literature Education, 2026)
This study was motivated by the low level of argumentative literacy among elementary school students, as indicated by their inability to construct claims, provide evidence, and develop logical reasoning. This study aimed to analyze the improvement of students’ argumentative literacy through deep learning-based Indonesian language instruction at SDN 3 Kemawi. The study employed a quantitative approach using a quasi-experimental design with a one-group pretest–posttest model. Data were collected through tests, observations, and documentation, and were analyzed using a paired sample t-test and N-gain calculation. The results revealed a significant improvement in students’ argumentative literacy skills, with the mean score increasing from 51.25 in the pretest to 75.75 in the posttest, and an N-gain value of 0.50, which falls into the moderate category. In addition, there was a noticeable change in students’ learning behavior, as they became more active, critical, and collaborative during the learning process. These findings indicate that deep learning-based instruction is effective in developing higher-order thinking skills and students’ argumentative literacy. This study implies that the implementation of student-centered learning with a meaningful learning approach can serve as a strategic alternative to improve the quality of Indonesian language instruction in elementary schools.